A preclinical model of chronic pancreatitis driven by trypsinogen autoactivation. Issue 1 (December 2018) - Geisz, Andrea; Sahin-Tóth, Miklós
Abstract Inflammatory diseases of the pancreas have no specific therapy. Discovery of the genetic basis of chronic pancreatitis identified the digestive enzyme trypsin as a therapeutic target. Preclinical testing of trypsin inhibition has been hampered by the lack of animal models. Here we report theT7D23A knock-in mouse, which carries a heterozygous p.D23A mutation in mouse cationic trypsinogen (isoform T7). This trypsinogen mutant autoactivates to trypsin 50-fold faster than wild type.T7D23A mice develop spontaneous acute pancreatitis with edema, necrosis and serum amylase elevation at an early age followed by progressive atrophic chronic pancreatitis with acinar cell loss, fibrosis, dilated ducts and adipose replacement. Markedly elevated trypsin activity is apparent at first signs of pancreatitis and persists into later stages of the disease. This remarkable model provides in vivo proof of concept that trypsinogen autoactivation can drive onset and progression of chronic pancreatitis and therapy should be directed against intra-pancreatic trypsin. Inflammatory diseases of the pancreas are currently untreatable and lack a pre-clinical model that recapitulates the hallmarks of the human pathology. Here, the authors generate a knock-in mouse strain with increased tripsinogen autoactivation and show that it develops spontaneous pancreatic pathology with some key features of human pancreatitis.